Penerapan model kooperatif tipe Think–Pair–Share (TPS) untuk meningkatkan komunikasi matematika siswa madrasah - Nabila, Aghistna (Maliki Interdisciplinary Journal, 2025)
Mathematical communication is a crucial aspect of mathematics education as it enables students to articulate ideas, comprehend concepts, and construct arguments clearly. Yet, classroom practices in madrasah remain largely teacher-centered, limiting opportunities for students to practice mathematical communication. This study aims to examine the effectiveness of the Think–Pair–Share (TPS) cooperative learning model in enhancing students’ mathematical communication skills. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation at an Islamic junior high school in Pasuruan. The findings reveal that TPS strengthens students’ communication abilities in three main indicators: explaining problem-solving steps, expressing mathematical ideas both orally and in writing, and providing logical arguments. Students became more engaged in discussions, more confident in sharing opinions, and better at organizing mathematical information systematically. This research contributes to the development of cooperative-based tadris mathematics and offers practical recommendations for teachers to optimize TPS in lessons requiring active communication.